1948
DOI: 10.1021/ja01186a081
|View full text |Cite
|
Sign up to set email alerts
|

Relative Rates of Propylation of Monoalkylbenzenes

Abstract: Relative Rates of Propylation of Monoalkylbenzenes 2265 described above, in about 60% yield. The m. p.'s and N contents of those not found in the literature are presented in Table I. Table I Phenylhydrazones of (3-Formylpropionic Acid Substituents of phenylhydrazine M. p., °C. cor., dec. Nitrogen, % Caled. Found 2-Nitro 155-156 17.7 17.4 17.4 2-Chloro 180-185. 5 12.4 12.3 12.2 2,4-Dichloro

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1952
1952
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Table 475 gives an idea of the procedure when sulphuric acid is used as catalyst. Consumption of acid in kg per kg alkylate [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Molar ratio of benzene to propene tetramer 3-5:1 Residence time, in hours 1 Ratio of acid to hydrocarbon 1:1 Oil-soluble high-molecular-weight salts of alkylarylsulphonates are used extensively as additives to motor lubricating oils. They are made from suitable lubricating oil fractions by sulphonation with oleum or "Sulfan".…”
Section: A the Alkylation Of Benzene With Propene Polymerizate In Thmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 475 gives an idea of the procedure when sulphuric acid is used as catalyst. Consumption of acid in kg per kg alkylate [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Molar ratio of benzene to propene tetramer 3-5:1 Residence time, in hours 1 Ratio of acid to hydrocarbon 1:1 Oil-soluble high-molecular-weight salts of alkylarylsulphonates are used extensively as additives to motor lubricating oils. They are made from suitable lubricating oil fractions by sulphonation with oleum or "Sulfan".…”
Section: A the Alkylation Of Benzene With Propene Polymerizate In Thmentioning
confidence: 99%
“…Consequently, the tendency to form polyalkyl derivatives is considerable and it is essential to use a large excess of aromatic hydrocarbons in order to force the polyalkylation into the background. Thus, the relative reaction velocities of various mono-alkylated aromatics as compared with benzene (reaction velocity = 1) are : toluene 2·1, ethylbenzene 1«8, isopropylbenzene (eumene) 1-7, t-butylbenzene 1*4 [12]. With multiplealkylated aromatics, certain positions of the substituents often markedly reduce the reactivity of the hydrocarbon.…”
mentioning
confidence: 99%
“…From relative rates of propylation of alkylbenzenes compared to benzene and from the ratios of isomers produced in propylation, Condon (21) calculated the partial rate factors for toluene and isopropylbenzene listed in table 6. (Recall that the partial rate factors are integers to express the probability of reaction at a given nuclear carbon atom compared to a carbon atom of benzene.) It is observed in table 6 that the partial rate factors for the meta and para positions of toluene and cumene are of the same magnitudes, so that the severalfold decrease for that of the ortho position of cumene can be attributed to a steric effect.…”
Section: Steric Effectsmentioning
confidence: 99%
“…From the studies of Andrews and Keefer (1) on the argentation of aromatic compounds and of Kharasch ( 52) on the hydrolysis of mercurials, aside from theoretical reasons, it can be deduced that the polarizabilities of halophenyl groups decrease in the order bromophenyl > chlorophenyl > fluo-® rophenyl. Hence, if nitration proceeds by the cation NO2, while halogenation involves only the neutral molecule, then the nitronium ion evokes a more TABLE 8 Orientation of various types of electrophilic substitutions (21,39,53) powerful polarization on the aromatic molecule and the difference in polarization activation will be greatest for iodobenzene and least for fluorobenzene.…”
Section: E Polarization By the Attacking Reagentmentioning
confidence: 99%
“…The postulation (13) of the formation of an intermediate trialkylated product followed by dealkylation hardly explains the formation of meta-orientated products from toluene and alkyl halides having large alkyl groups. Condon (14) showed that meta alkylation proceeds by a direct rather than by an isomerization or an alkylation-dealkylation process. Hennion, Driesch, and Dee (15) have recently demonstrated that the preponderance of the para isomer in the ¿ert-butylation of isopropylbenzene and that of the meta isomer in the isopropylation of iert-butylbenzene could be explained only on the basis of the steric factor involved.…”
mentioning
confidence: 99%